Complexes of Zinc(II), Cadmium(II) and Mercury(II) Perchlorates with Substituted Benzimidazoles - Donappa, N.; Naikar, S.B. (Asian Journal of Chemistry, 2010)
A series of zinc(II), cadmium(II) and mercury(II) perchlorate complexes of the general formulae MLn(ClO4)2 (M = Zn(II), Cd(II) and Hg(II); L = 2,6- bis(2-bezimidazyl) pyridine-(bBzIH2Py), 2-(2´-quinolyl) benzimidazole (2-QylBzIH), 2,2´-bis-(benzimidazyl) sulphide (bBzIH2S), and 2,2´-bis(benzimidazyl)-ethane (bBzIH2e) (n = 1 or 2) have been prepared and characterised by conductivity, IR and proton NMR spectra. IR spectra give evidence for co-ordination of perchlorate in most of these complexes.